Pragmática das perguntas Como P, se Q? e Como não P, se Q? - Fonseca, Joaquim (1993)
In this study the author analyses how questions of the format "Como p, se q?" (How p, if q?) and "Como não p, se q?" (How not p, if q?) work in Portuguese discourse. Some relevant pragmatic features of these questions are emphasized.